Development of Ludo Math Props to Improve Student Learning Interest in Logarithm Material - Rahmawati, Tia; Zalisca, Zelvy Salsabila; Mahera, Pipit; Ramandhika, Muhammad Fauzan; Susanti, Elsa; Meryamsumayeka, Meryamsumayeka; Zulkardi, Zulkardi (Phenomenon : Jurnal Pendidikan MIPA, 2024)
This study aims to develop learning media in the form of LUDO MATH that can increase student interest in learning Logarithms. This type of research is R & D using the ADDIE development model which consists of analysis, design, development, implementation, and evaluation. Data collection in this study was carried out by means of observation and interviews. Descriptive analysis is used to describe the results of the development of LUDO MATH from the analysis to evaluation stage. The results of the material expert validation showed that LUDO MATH media obtained a percentage of 80% in the valid category. While the results of the media expert validation obtained a percentage of 80% with a valid category. For the assessment of the practicality of teaching aids seen from the results of the assessment by teachers and students. Where the results of the assessment by the teacher obtained a percentage of 76.67% with a practical category, while the results of the assessment by students obtained a percentage of 84.55% with a very practical category. To see the effectiveness of teaching aids, it is seen from the results of observations during the trial and supported by the results of interviews on the trial subjects. The results showed that the LUDO MATH learning media developed proved to be valid, effective, and practical so that the use of this media can be an alternative for teachers in increasing student interest in learning Logarithms.